2020
DOI: 10.1186/s43162-020-00007-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atorvastatin on inflammatory markers in hemodialysis patients

Abstract: Background Cardiovascular disease is the commonest cause of death in patients with end-stage renal disease (ESRD) under maintenance hemodialysis. Dyslipidemia, oxidative stress, and low-grade inflammation with increased circulating cytokines are factors that increase the cardiovascular risk in patients with chronic kidney disease, in addition to traditional risk factors, such as obesity, hypertension, and diabetes. We aimed to investigate the possible anti-inflammatory effects of atorvastatin in prevalent hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Dialysis patients were included in 14 studies [ 39 42 , 45 , 46 , 48 , 51 55 , 61 , 63 ], and CKD patients were included in 11 studies [ 43 , 44 , 47 , 49 , 50 , 56 60 , 62 ]. Patients received fluvastatin in 3 studies [ 39 , 43 , 53 ], rosuvastatin in 7 studies [ 40 , 45 , 48 , 51 , 59 , 60 , 62 ], atorvastatin in 8 studies [ 44 , 46 , 47 , 50 , 52 , 54 , 56 , 63 ], simvastatin in 4 studies [ 41 , 55 , 58 , 61 ], lovastatin in 1 study [ 50 ], and pravastatin in 2 studies [ 42 , 57 ]. The dosage of statins was ranged from 5 mg to 80 mg daily.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dialysis patients were included in 14 studies [ 39 42 , 45 , 46 , 48 , 51 55 , 61 , 63 ], and CKD patients were included in 11 studies [ 43 , 44 , 47 , 49 , 50 , 56 60 , 62 ]. Patients received fluvastatin in 3 studies [ 39 , 43 , 53 ], rosuvastatin in 7 studies [ 40 , 45 , 48 , 51 , 59 , 60 , 62 ], atorvastatin in 8 studies [ 44 , 46 , 47 , 50 , 52 , 54 , 56 , 63 ], simvastatin in 4 studies [ 41 , 55 , 58 , 61 ], lovastatin in 1 study [ 50 ], and pravastatin in 2 studies [ 42 , 57 ]. The dosage of statins was ranged from 5 mg to 80 mg daily.…”
Section: Resultsmentioning
confidence: 99%
“…For IL-6, 8 studies [ 44 , 45 , 47 , 50 , 52 , 55 , 56 , 61 ] were included in the meta-analysis, and the pooled results showed that there was no significant difference between the statin and control groups (0.1 pg/mL; 95% CI: -0.93 to 1.13, p = 0.85). For TNF- α , 4 studies [ 47 , 50 , 55 , 61 ] were included in the meta-analysis, and the pooled results showed that there was no significant difference between the statin and control groups (-7.06 pg/mL; 95% CI: -14.49 to 0.38, p = 0.06).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation